Cirrhosis Hampers Early and Rapid Normalization of Natural Killer Cell Phenotype and Function in Hepatitis C Patients Undergoing Interferon-Free Therapy - Perpiñán, Elena; Pérez-Del-Pulgar, Sofía; Londoño, María-Carlota; Mariño, Zoe; Bartres, Concepción; González, Patricia; García-López, Mireia; Pose, Elisa; Lens, Sabela; Maini, Mala K.; Forns, Xavier; Koutsoudakis, George (Frontiers in Immunology, 2020)
Background: Chronic hepatitis C virus (HCV) infection impairs natural killer (NK) cell phenotype and function. Whether restoration of NK cells occurs after successful interferon (IFN)-free therapies remains a controversial issue. Aim: To analyze how HCV-related liver cirrhosis impacts changes in NK cells prior and post-IFN-free therapies. Methods: NK cell analysis by multicolor flow cytometry was performed in HCV-infected patients with (n = 17) and without (n = 14) cirrhosis at baseline, week 4 during therapy, and weeks 12 and 48 after the end of therapy (FU12 and FU48, respectively). Non-HCV cirrhotic patients (n = 12) and healthy individuals (n = 12) served as controls. Results: At baseline, HCV cirrhotic patients presented an altered distribution of NK subsets (CD56dim and CD56bright) with higher expression of NKp46, HLA-DR, NKp30, KIR2DL2/L3, NKG2A, and CD85j receptors compared to healthy controls. All frequencies normalized by FU48, except for CD85j+ cells. Likewise, substantial alterations were detected in NK cell function assessed by (i) signal transducer and activator of transcription 1 (STAT1) and phosphorylated levels of STAT1 and STAT4, (ii) degranulation (CD107a), (iii) cytotoxicity [tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)], and (iv) cytokine production [IFN-γ and tumor necrosis factor-α (TNF-α)]. Of note, NK cell function at FU48 remained partially impaired. In contrast, non-cirrhotics showed normal baseline frequencies of HLA-DR-, NKG2A-, and CD85j-expressing NK cells. Importantly, altered baseline frequencies of NK cell subsets and NKp46+ CD56dim cells, as well as NK cell function, were rapidly and completely restored. Conclusions: NK cell phenotype alterations persist after HCV eradication in cirrhotic patients, while their function is only partially restored, compromising immune restoration and immunosurveillance.